PENGARUH INTERNET FINANCIAL REPORTING TERHADAP FREKUENSI PERDAGANGAN SAHAM DENGAN TINGKAT PENGUNGKAPAN INFORMASI WEBSITE SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA SELURUH PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2018) - Dewi Andini Latif Duka; Fadli Ali Taslim (Jurnal Manajemen Sinergi, 2020)
Objective: The purpose of this study are: (1) To find out andanalyze Internet Financial Reporting (IFR) affect the frequencyof stock trading in all companies listed on the Indonesia StockExchange; (2) To find out and analyze the role of websiteinformation disclosure level in strengthening the relationshipbetween Internet Financial Reporting on the frequency of stocktrading in all companies listed on the Indonesia StockExchange.Methodology: The number of research samples were 531companies. The test tool used is a moderated regressionanalysis (MRA) using statistical package for social scientists(SPSS) as a statistical test tool.Finding: H1 H2, and H3 are accepted at the 5% confidencelevel.Conclusion: The results showed that: (1) Internet FinancialReporting has a positive and partially significant effect on thefrequency of stock trading in all companies listed on theIndonesia Stock Exchange in 2018. The results of this studymean that, companies that apply IFR can increase thefrequency of stock trading; (2) The level of website informationdisclosure as a moderating variable has a positive andsignificant effect. The results of this study mean that the level ofwebsite information disclosure strengthens the relationshipbetween internet financial reporting and the frequency of stocktrading. And the more levels of information disclosure canincrease the frequency of stock trading.